Behaviour of cellular beams protected with intumescent coatings - Lamri, Brahim (2018)
A new engineering practice in modern buildings is to use beams with web openings to allow the passage of services within the depth of the beam instead of underneath the beam. This helps to reduce the floor height of the building and optimises the available space. The openings are cut in the web of a beam or a beam profile cut and re-welded to form the so called cellular beam. Usually the bending resistance is increased, in comparison to the original solid section, but the failure mode occurs generally at lower critical temperatures. The failure mode in fire is related to the distance between holes, web post slenderness in addition to the web and flange section factor. The loss of the beam strength with temperature promotes an early web post failure that occurs before the section reaches the critical temperature, reason why an increase in the fire protection may be required for these beams to achieve the same fire resistance time as the equivalent solid beams. Recent research on beams with closely spaced web openings has shown that the web posts between adjacent openings become significantly hotter than the bottom flange of the section, and that web post buckling can often be the failure mode for a member in the fire condition. The present study aims at investigating the behaviour of cellular beams under fire conditions when considering unprotected and intumescent protected cellular steel beams. Experimental tests are conducted in both cases with and without protection where temperature profiles are produced and analysed. The behaviour of the intumescent fire protection with different properties and thicknesses is studied and compared using fire resistance tests. Simplified method of analysis and finite element models are used to study and compare results from tests. The experimental temperature results show intumescent coating efficiency when applied to solid beams and also for cellular beams, resulting from its application an increase fire the resistance time in both cases. Considering for example the time required for the steel to reach 550 [ºC], with the application of a nominal thickness of 1000 [m], an increase of the fire resistance time of 25 minutes is achieved for solid beams, while for cellular beams with a hole diameter of 160[mm] the increase is equal to 17 minutes. Tests performed in cellular beams with web posts of 80 and 100 [mm] does not show any significate temperature difference neither in relation to the fire resistance time. For both beams, when is applied a nominal DFT equal to 1000 [m], the temperature of 550 [ºC] is achieved after 28 minutes. For longer fire exposure periods a slight difference can be already verified. For the case of a cellular beam with intumescent coating, test P16, a small contraction of the intumescent char around the circular hole, leaving a small area of steel directly exposed to fire. This study is being extended to a wider parametric analysis considering different cellular beams geometries and intumescent coatings thicknesses to allow for a general elemental multi-temperature analysis (EMTA).